Addition of Berberine to Preservation Solution in an Animal Model of Ex Vivo Liver Transplant Preserves Mitochondrial Function and Bioenergetics from the Damage Induced by Ischemia/Reperfusion - Martins, Rui Miguel (2018)
Liver transplantation is a therapeutic regimen to treat patients with non-malignant end-stage liver diseases and malignant tumors of hepatic origin. The ischemia/reperfusion (I/R) injury in liver transplantation is associated with disruption of mitochondrial function in the hepatic parenchyma. Several studies have been conducted in animal models to identify pharmacological therapeutic strategies to minimize the injury induced by the cold/warm I/R in liver transplantation. Most of these studies were conducted in unrealistic conditions without the potential to be translated to clinical usage. Berberine (BBR) is a pharmacological compound with a potential protective effect of the mitochondrial function in the context of I/R. For the future clinical application of these pharmacological strategies, it is essential that a close resemblance exists between the methodology used in the animals models and real life. In this study, we have demonstrated that the addition of BBR to the preservation solution in an I/R setting preserves mitochondrial function and bioenergetics, protecting the liver from the deleterious effects caused by I/R. As such, BBR has the potential to be used as a pharmacological therapeutic strategy.